A personal character model of affect, behavior and cognition for individual-like research. (January 2020) - Guo, Ao; Ma, Jianhua; Sun, Guanqun; Tan, Shunxiang
Abstract: Humanoid robots, avatars, as well as some machines or tools possessing distinctive human features or characteristics, have been studied and developed in recent years. Alongside these developments, a new research area has emerged, known as individual-like research, the aim of which is the creation of physical or digital entities that resemble, to a certain extent, an existing human individual. Such individual-like entities could generate novel and as yet undreamed-of applications in fields such as lifestyle management. A general or comprehensive model of an individual's character is the key to individual-like research. Derived from the personality model in psychology, this paper proposes a structuralized and computable model, namely the Personal Character Model of affect, behavior and cognition (ABC). We first assign mathematical abstractions to the proposed personal character model, then present a general computing process of personal character in the model, and finally perform an experiment to collect the state data of twenty subjects and further analyze the results pertaining to personal emotional stability and attention ability, as well as the relational characteristic of each subject's affect and cognition.